ANALISIS RENDAHNYA KUALITAS SUMBER DAYA MANUSIA DAN POTENSI SUMBER DAYA ALAM PESISIR DI KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Susilawati Susilawati; Lisa Aulia Rahmah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The coastal area is the meeting area between land and sea. In coastal areas there is a wealth of coastal resources in the form of natural resources and environmental services which are very abundant. Natural resources found in coastal areas have important meaning in fishing activities, environmental conservation, marine tourism, and environmental services related to people's welfare. To maintain the potential of these natural resources, quality human resources are needed that are able to preserve the potential of existing natural resources. This study aims to determine the quality of human resources and the potential of coastal natural resources in Serdang Bedagai Regency, North Sumatra. This research method is a literature review using a narrative approach by classifying, collecting, differentiating, evaluating, and interpreting the collected information which is similar to the measurement results that have been carried out. The library sources used in compiling this literature review are through national journal websites such as Google Scholar. The conclusion from the results of the literature review explains that the human resources of traditional fishermen in the coastal area of Serdang Bedagai Regency are generally still very low. This can be seen from the low level of education of fishermen. In addition, the Serdang Bedagai coastal area has a lot of potential natural resources including fishing activities, mangrove ecotourism and marine tourism